Quality evaluation of synthetic quorum sensing peptides used in R&D - Frederick Verbeke; Evelien Wynendaele; Sarah Braet; Matthias DâHondt; Bart De Spiegeleer (Elsevier, 2015)
Peptides are becoming an important class of molecules in the pharmaceutical field. Closely related peptide-impurities in peptides are inherent to the synthesis approach and have demonstrated to potentially mask biomedical experimental results. Quorum sensing peptides are attracting high interest in R&D and therefore a representative set of quorum sensing peptides, with a requested purity of at least 95.0%, was evaluated for their purity and nature of related impurities. In-house quality control (QC) revealed a large discrepancy between the purity levels as stated on the supplier×³s certificate of analysis and our QC results. By using our QC analysis flowchart, we demonstrated that only 44.0% of the peptides met the required purity. The main compound of one sample was even found to have a different structure compared to the desired peptide. We also found that the majority of the related impurities were lacking amino acid(s) in the desired peptide sequence. Relying on the certificates of analysis as provided by the supplier might have serious consequences for peptide research, and peptide-researchers should implement and maintain a thorough in-house QC. Keywords: Quorum sensing peptides, Quality, Impurity profiling